Reconstruction of the Medial Canthus Using an Ipsilateral Paramedian Forehead Flap - Kim, Jin Hyung; Kim, Jeong Min; Park, Jang Wan; Hwang, Jae Ha; Kim, Kwang Seog; Lee, Sam Yong (Archives of Plastic Surgery, 2013)
Background The medial canthus is an important area in determining the impression of a person's facial appearance. It is composed of various structures, including canthal tendons, lacrimal canaliculi, conjunctiva, the tarsal plate, and skin tissues. Due to its complexity, medial canthal defect reconstruction has been a challenging procedure to perform. The contralateral paramedian forehead flap is usually used for large defects; however, the bulkiness of the glabella and splitting at the distal end of the flap are factors that can reduce the rate of flap survival. We reconstructed medial canthal defects using ipsilateral paramedian forehead flaps, minimizing glabellar bulkiness.Methods This study included 10 patients who underwent medial canthal reconstruction using ipsilateral paramedian forehead flaps between 2010 and 2012. To avoid an acute curve of the pedicle, which can cause venous congestion, we attempted to make the arc of the pedicle rounder. Additionally, the pedicle was skeletonized from the nasal root to the glabella to reduce the bulkiness.Results All patients had basal cell carcinoma, and 3 of them had recurrent basal cell carcinoma. All of the flaps were successful without total or partial flap loss. Two patients developed venous congestion of the flap, which was healed using medicinal leeches. Four patients developed epiphora, and 2 patients developed telecanthus.Conclusions Large defects of the medial canthus can be successfully reconstructed using ipsilateral paramedian forehead flaps. In addition, any accompanying venous congestion can be healed using medicinal leeches.
Keywords: Forehead; Surgical flaps; Leeches; Carcinoma